Occupational health safety in aquaculture: A case study on semi-intensive shrimp farmers of Bangladesh - Md Mostafizur Rahman; Md. Khaladur Rahman Shohag; Md. Ridwanul Islam; Md Shamim Hasan; Jinat Ara Nasrin; Mst. Muslima Khatun; Sudip Debnath; Md. Moshiur Rahman; Edris Alam; Khawla Saeed Al Hattawi; Md Kamrul Islam; Abu Reza Md. Towfiqul Islam (PLoS ONE, 2025)
The study examined health safety issues among semi-intensive shrimp farmers in southwestern Bangladesh. The study assessed semi-intensive shrimp farmers’ knowledge, attitudes, and practices (KAP) on health and safety during their farm activities. The KAP model examined working circumstances, exposures, health complaints, diseases, current health status, and job satisfaction. Face-to-face interviews were conducted with 158 semi-intensive shrimp farmers from Bangladesh’s Khulna, Satkhira, and Bagerhat districts. Type-based data analysis was done. We used Spearman’s rank correlation and multiple linear regression. Only 35% of respondents said that they knew the health safety of chemicals and pesticides used in semi-intensive shrimp farms and that safety training is needed, and all farmers wanted to attend when available. At least 74% of farmers used masks when handling pesticides, fertilizers, and chemicals. 40.50% of farmers used protective clothing, 91% cleansed their hands, legs, and face after each day’s work, and 94% felt that sanitization reduces pesticide, fertilizer, and chemical pollution. A significant positive correlation coefficient was established in KAP. Education significantly increased knowledge. Practices varied with health and safety training. Results suggest that attitudes determine practices, where knowledge is significantly associated with attitudes. A comprehensive health safety and hygiene training program for all shrimp farmers should be developed to raise awareness, reduce illness outbreaks, and preserve healthy living.